2001
DOI: 10.2310/6650.2001.33785
|View full text |Cite
|
Sign up to set email alerts
|

Increased Soluble P-Selectin Levels in Hepatitis C Virus-Related Chronic Hepatitis: Correlation with Viral Load

Abstract: The results obtained in this study support the hypothesis that HCV infection might be directly responsible for a condition of in vivo platelet activation in patients with chronic C hepatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 22 publications
1
16
0
1
Order By: Relevance
“…Moreover, sP-s levels were even higher in patients with a platelet count lower than 110 x 10 3 μL, independently of the presence of plateletassociated immunoglobulins [6]. In addition, a likely direct HCV activation of platelets could be hypothesized based on a strong positive correlation between sP-s/platelet levels and HCV viral load [6]. All together, these results suggested that in vivo platelet activation and degranulation might take place as a direct consequence of HCV infection, leading to the presence of exhausted platelets (not responding to further in vitro stimulation) that are subsequently removed from the circulation with resultant TCP.…”
Section: Dear Editormentioning
confidence: 88%
See 3 more Smart Citations
“…Moreover, sP-s levels were even higher in patients with a platelet count lower than 110 x 10 3 μL, independently of the presence of plateletassociated immunoglobulins [6]. In addition, a likely direct HCV activation of platelets could be hypothesized based on a strong positive correlation between sP-s/platelet levels and HCV viral load [6]. All together, these results suggested that in vivo platelet activation and degranulation might take place as a direct consequence of HCV infection, leading to the presence of exhausted platelets (not responding to further in vitro stimulation) that are subsequently removed from the circulation with resultant TCP.…”
Section: Dear Editormentioning
confidence: 88%
“…Scheuer Score equal to 4) had higher levels of plasma sP-s, normalized by platelet counts (sP-s/platelet), compared with those with mild-moderate disease [6]. Moreover, sP-s levels were even higher in patients with a platelet count lower than 110 x 10 3 μL, independently of the presence of plateletassociated immunoglobulins [6].…”
Section: Dear Editormentioning
confidence: 96%
See 2 more Smart Citations
“…Although this interpretation cannot be fully supported by the data of 11-deydro-TxB2 urinary excretion as it only partly reflects the activation of platelet COX1 [130], other studies also seem to support the existence of enhanced platelet activation in cirrhosis. Soluble P-selectin (sPs), which is an in vivo marker of platelet activation is consistently elevated in plasma particularly in cases of severe liver disease and correlated with markers of hepatic protein synthesis and low platelet counts [131][132][133].…”
Section: Thrombocytopathy In Liver Cirrhosismentioning
confidence: 99%